Attitude to one's own body and features of interaction with sibling in teenage girls - Bulygina, M.V.; Novitskaya, S.L. (Konsulʹtativnai͡a︡ psikhologii͡a︡ i psikhoterapii͡a, 2025)
Context and relevance. The study of attitudes towards the body does not lose its relevance, since dissatisfaction with one's appearance increases the likelihood of serious mental disorders. Most studies record a violation of family, primarily child-parent, relationships in people who are dissatisfied with their own bodies. In this paper, attention is focused on a less obvious aspect - sibling relationships and their role in shaping attitudes towards one's own body. The relevance of this study is due to the fact that various relationships with brothers and sisters in the process of forming a self-relationship can be both a support zone and a trauma zone. Objective. To study the representation of attitudes towards one's own body in older adolescent girls with and without siblings, and to identify factors of sibling interaction associated with the degree of satisfaction with one's own body. Hypothesis. 1) dissatisfaction with one's own body is higher among girls who have sisters (since having a same-sex sibling contributes to competition in the area of ​​external attractiveness); 2) the characteristics of sibling relationships are associated with the attitude towards the body (in emotionally close relationships, the body is perceived by girls more positively, and in negative relationships, dissatisfaction with one's own body increases). Methods and materials. Dissatisfaction with one's own body increases). Methods and materials. The study involved 129 girls aged 15-17 (M = 15.84; SD = 0.785) from two-child (N=89: 51 are the oldest children in the family; 38 are the youngest) and one-child (N=40) families. Methods: Multidimensional Body-Self Relations Questionnaire (MBSRQ) T.F. Cash; The questionnaire of the image of one's own body (OOST) O.A. Skugarevsky, S.V. Sivukha; Brother-sister questionnaire (BSQ) S.A. Graham-Berman, S.E. Gulter, adapted by M.V. Kravtsova; Lifespan Sibling Relationship Scale Items (LSRSI) H. Riggio, adapted by O.V. Almazova. Results. The results of the study revealed that there is no linear relationship between satisfaction with one's own body in older teenage girls and the presence of sibling. Nevertheless, the combination of factors of sibling gender, birth order, age difference between children in the family and the nature of sibling relationships are significant for the formation of girls' attitudes to their own bodies. Conclusions. The highest level of dissatisfaction with one's own body was found in girls who had a younger sibling with an age difference of no more than five years; In same-sex sibling relationships, body dissatisfaction in older sisters is higher than in younger sisters; Girls who have sisters rate their appearance lower than girls who have brothers; Girls' concern about excess weight is associated with the negative nature of sibling relationships; Close, empathic relationships with brothers are associated with girls with higher self-assessments of appearance. Контекст и актуальность. Изучение отношения к телу не теряет своей актуальности, поскольку неудовлетворенность своим внешним обликом повышает вероятность возникновения серьезных психических нарушений. Большинство исследований фиксирует у лиц, неудовлетворенных собственным телом, нарушение семейных, в первую очередь детско-родительских, отношений. В данной работе внимание сконцентрировано на менее очевидном аспекте - сиблинговых отношениях и их роли в формировании отношения к собственному телу. Актуальность данного исследования обусловлена тем, что различные отношения с братьями и сестрами в процессе формирования самоотношения могут быть как зоной поддержки, так и зоной травматизации. Цель. Изучение отношения к собственному телу у девушек старшего подросткового возраста, имеющих и не имеющих сиблинга, и выявление факторов сиблингового взаимодействия, связанных со степенью удовлетворенности собственным телом. Гипотезы: 1) неудовлетворенность собственным телом выше у девушек, имеющих сестер (поскольку наличие однополого сиблинга способствует конкуренции в сфере внешней привлекательности); 2) особенности сиблинговых отношений связаны с отношением к телу (при эмоционально-близких отношениях тело воспринимается девушками более позитивно, а при негативных отношениях повышается неудовлетворенность собственным телом). Методы и материалы. Выборка: в исследовании приняли участие 129 девушек 15-17 лет (M = 15,84; SD = 0,785) из двудетных (n = 89: 51 - старшие дети в семье; 38 - младшие) и однодетных семей (n = 40). Методики: «Мультимодальный опросник отношения к собственному телу» Т.Ф Кэша (MBSRQ); «Опросник образа собственного тела» О.А. Скугаревского, С.В. Сивухи (ООСТ); «Братско-сестринский опросник» С.А. Грехем-Берман, С.Э. Гултер (BSQ), в адаптации М.В. Кравцовой; «Шкала сиблинговых отношений на протяжении жизни» Х. Риджио (LSRSI), в адаптации О.В. Алмазовой. Результаты. Результаты исследования выявили, что отсутствует линейная связь между удовлетворенностью собственным телом у девушек старшего подросткового возраста и наличием у нее сиблинга. Тем не мене сочетание факторов пола сиблинга, порядка рождения, разницы в возрасте между детьми в семье и характера сиблинговых отношений значимы для формирования отношения девушек к собственному телу. Выводы. Наиболее высокий уровень неудовлетворенности собственным телом выявлен у девушек, имеющих младшего сиблинга с разницей в возрасте не более пяти лет; при однополых сиблинговых отношениях неудовлетворенность телом у старших сестер выше, чем у младших сестер; девушки, имеющие сестер, ниже оценивают свой внешний вид, чем девушки, имеющие братьев; озабоченность девушек излишним весом связана с негативным характером сиблинговых отношений; Близкие, эмпатичные отношения девушек с братьями связаны с более высокой самооценкой внешности.